A preliminary assessment of the presence and distribution of invasive and potentially invasive alien plant species in Laikipia County, Kenya, a biodiversity hotspot - Arne B.R. Witt (Koedoe: African Protected Area Conservation and Science, 2020)
This is the first assessment of naturalised, invasive and potentially invasive alien plant species present in Laikipia County, Kenya, which hosts the highest populations of endangered large mammals in the country. We undertook broad-scale roadside surveys in Laikipia, recording all naturalised and invasive species, and based on an extensive literature review, also compiled a list of those alien species present that are known to threaten biodiversity and livelihoods elsewhere in the world. The data were supplemented by CLIMEX eco-climatic niche models of nine species that we consider to pose the biggest threat to conservation initiatives in the East African region. Of the 145 alien plant species recorded, 67 and 37 (including four species of uncertain origin) were considered to be already naturalised or invasive, respectively, and a further 41 species had been recorded as being naturalised or invasive outside of Laikipia. Most (141) of these species were introduced as ornamentals only or had uses in addition to being ornamentals, with the majority (77) having their origins in tropical America. Widespread species in the county included Opuntia stricta, O. ficus-indica, Austrocylindropuntia subulata and other succulents. Based on the current eco-climatic conditions, most of Laikipia is unsuitable for Chromolaena odorata, marginally suitable for Mimosa pigra and Lantana camara, and a better climatic match, ranked from least to most favourable, for Tithonia diversifolia, Cryptostegia grandiflora, Parthenium hysterophorus, Prosopis juliflora, O. stricta and Parkinsonia aculeata.